The End is Always Near : Apocalyptic Moments, From the Bronze Age Collapse to Nuclear near Misses - Carlin, Dan (New York Harper Collins Publishers, 2019)
"A journey back in time that explores what happened -- and what could have happened -- from creator of the wildly-popular podcast Hardcore History and 2019 winner of the iHeartRadio Best History Podcast Award"--
Include Index
Keywords: World history -- Civilization -- Imaginary histories